High Genetic Similarity of MRSA ST88 Isolated From Pigs and Humans in Kogi State, Nigeria - Otalu, Otalu Jnr; Kwaga, Jacob K. P.; Okolocha, Emmanuel Chukuwdi; Islam, Md Zohorul; Moodley, Arshnee (Frontiers in Microbiology, 2018)
We determined the prevalence and genetic characteristics of methicillin-resistant Staphylococcus aureus (MRSA) isolated from pigs and humans between September 2013 and February 2015 in Kogi State, a central region in Nigeria. A total of 680 nasal swabs were collected and analyzed from pigs (n=425) and ‘pig-contact’ humans (n=55) on 35 farms, and ‘non pig-contact’ humans (n=200). MRSA was recovered from 20 (4.7%) pigs on 12 farms and 18 (7.0%) humans. Six (2.4%) of the human isolates were recovered from ‘pig-contact’ humans, of which only three work on farms also harboring MRSA positive pigs. All 38 MRSA were resistant to β-lactams only, belonged to spa type t1603, sequence type (ST) 88, and mecA was associated with a SCCmec IVa element. Four isolates from a pig, a pig-contact human from the same farm, a pig-contact human from a pig farm in a different district, and a non pig-contact human were subjected to whole genome sequencing. Core genome SNP analysis revealed high genetic similarity between strains (3-11 SNP differences), despite the temporal (2 year gap) and geographic (165km) differences between isolates. Furthermore, these Nigerian isolates form a distinct clade when compared to other African MRSA ST88 isolates. All but one porcine strain was positive for scn suggesting a possible human origin and that pigs were either transiently contaminated by humans or result of a very recent human-to-pig transmission event. To our knowledge, this is the first report of genetically confirmed MRSA in pigs in Nigeria, which appear to be a typical CA-MRSA clone present in the human population.